2017
DOI: 10.1111/vde.12472
|View full text |Cite
|
Sign up to set email alerts
|

Determination of irritant threshold concentrations of multiple tree, grass, weed and mould allergens for intradermal testing of horses residing in the southern USA

Abstract: This study identified intradermal TC for multiple pollen and mould allergens in horses. These values may prove useful for optimizing allergen concentrations for IDT of allergic horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…IDTs were, until now, considered the most sensitive and confirmatory skin tests for horses [16,24,26,36], and although some authors still argue in favor of IDTs [37], according to others [2], allergic horses may sometimes present several positive reactions to multiple allergens in IDTs, even to those allergens that are unlikely to cause allergies. Multiple studies over the years have shown that even healthy horses can react to IDTs [12,[36][37][38], which can frequently induce false positive reactions in clinically healthy individuals [39,40]. This may represent an additional challenge to identify the allergens that truly induce disease.…”
Section: Discussionmentioning
confidence: 99%
“…IDTs were, until now, considered the most sensitive and confirmatory skin tests for horses [16,24,26,36], and although some authors still argue in favor of IDTs [37], according to others [2], allergic horses may sometimes present several positive reactions to multiple allergens in IDTs, even to those allergens that are unlikely to cause allergies. Multiple studies over the years have shown that even healthy horses can react to IDTs [12,[36][37][38], which can frequently induce false positive reactions in clinically healthy individuals [39,40]. This may represent an additional challenge to identify the allergens that truly induce disease.…”
Section: Discussionmentioning
confidence: 99%
“…6 Furthermore, multiple studies over the years have shown that even healthy horses can react differently with intradermal tests, which is one of the reasons why the determination of thresholds for allergens is so difficult in horses. 5,[18][19][20] However, from human studies, it is known that the repeatability of a skin prick test for birch pollen, grass pollen, D. farinae and D. pteronyssinus is high in symptomatic allergic individuals. 21 Based on our results, only the IDT results of D. farinae, L. destructor, perennial rye and birch pollen mixture can be reliably assessed at 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, discrepancies in reactivity have been reported when comparing the two sides of the neck in atopic horses in one study 200 . Two studies attempted to determine threshold concentrations of allergens for skin testing – what concentration is less likely to induce an irritant reaction and most likely to induce a clinically relevant reaction 201,202 . Interestingly, both studies cast doubt on the clinical relevance of interpreting skin test reactions at 24 h post‐test.…”
Section: Atopic Dermatitismentioning
confidence: 99%